Coaching athletes to be their best. Motivational interviewing in sports - Rollnick, S.; Fader, J.; Breckon, J.; Moyers, T. B. (Guilford Press, 2020)
The measure of a great coach is bringing the best out of athletes. This is the first guide to motivational interviewing (MI)--the proven approach to harnessing the power of conversations to build relationships and trust--for coaches, sport psychologists, training and rehabilitation specialists, and other affiliated staff. Revealing why conventional ways of giving feedback and addressing conflict are often counterproductive, the book presents tried-and-tested methods for getting through to athletes and helping them to thrive. Leading sport psychologists and MI experts--including MI cofounder Stephen Rollnick--provide effective strategies to fire up motivation, promote ownership of personal goals, address problem behavior on and off the field, enhance performance, and improve teamwork. Included are step-by-step examples and inspiring stories from coaches at all levels. Purchasers get access to a Web page where they can download and print the book's reproducible quick-reference sheets on key MI skills.